HYDROCARBON INCLUSIONS IN SYNTHETIC DIAMONDS - Tomilenko A.A.; Chepurov A.I.; Pal'yanov Y.N.; Shebanin A.P.; Sobolev N.V. (My University, 1998)
Primary (syn-growth) fluid inclusions in synthetic diamonds, produced within the field of their thermodynamic stability in a high-pressure split-sphere apparatus using the temperature gradient method, have been studied by optical microscopy and Raman spectroscopy. Inclusions in tabular diamond crystals contain CH4 + other higher molecular hydrocarbons, whereas inclusions in octahedral and dodecahedral diamonds contain only CH4. All inclusions in octahedral and dodecahedral diamonds contain graphite, which covers the walls of vacuoles as an opaque film. The formation of this film is most likely associated with precipitation of carbon from fluid on cooling. The obtained results emphasize the possible role of hydrocarbons in the process of diamond crystallization.